2017
DOI: 10.1021/acs.molpharmaceut.6b00979
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–Drug Nanoparticles Combine Doxorubicin Carrier and Heparin Bioactivity Functionalities for Primary and Metastatic Cancer Treatment

Abstract: Here, a biocompatible amphiphilic copolymer of low molecular weight heparin (LMWH) and doxorubicin (DOX) connected by an acid-sensitive hydrazone bond for enhanced tumor treatment efficacy and safety has been designed and tested. The conjugate combines DOX delivery with LMWH antimetastatic capabilities. After the nanoparticles reach the tumor site, the acidic tumor microenvironment triggers the breakage of the hydrazone bond releasing DOX from the nanoparticles, which results in an increase in the cellular upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…On the contrary, after incubation with LWMH-containing formulations, both CHT NPs and free LMWH, the relative widths were 0.86 ± 0.06 and 0.79 ± 0.04 ( Figure 8(B) ), respectively, suggesting a reduced healing ability. The inhibitory effect against cell motility could be attributed to the presence of LMWH, which has been reported in previous work (Mei et al., 2016 ; Debele et al., 2017 ; Mei et al., 2017 ). Additionally, the wound width of CHT NPs and LMWH-treated groups showed no significance, indicating that the CHT NPs could well preserve this inhibitory effect of LMWH, which made this LWMH-based nanoplatform promising in exhibiting anti-metastasis activity.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…On the contrary, after incubation with LWMH-containing formulations, both CHT NPs and free LMWH, the relative widths were 0.86 ± 0.06 and 0.79 ± 0.04 ( Figure 8(B) ), respectively, suggesting a reduced healing ability. The inhibitory effect against cell motility could be attributed to the presence of LMWH, which has been reported in previous work (Mei et al., 2016 ; Debele et al., 2017 ; Mei et al., 2017 ). Additionally, the wound width of CHT NPs and LMWH-treated groups showed no significance, indicating that the CHT NPs could well preserve this inhibitory effect of LMWH, which made this LWMH-based nanoplatform promising in exhibiting anti-metastasis activity.…”
Section: Resultssupporting
confidence: 75%
“…Taken all together, the aim of this work is to fabricate a redox-responsive theranostic nanoplatform, which could realize an effective NIR imaging-guided combinational photodynamic/chemotherapy in a redox-triggered manner. In this study, low molecular weight heparin (LMWH) was innovatively utilized as the main component of the smart polymeric nanoplatform considering its non-toxicity, anti-metastasis, and anti-angiogenesis properties (Mei et al., 2016 , 2017 ; Yang et al., 2017b ). As depicted in Figure 1 , Ce6 was conjugated to LMWH backbone via cystamine, which could endow the nanosystem a redox-responsive property due to the presence of disulfide bond.…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymers have been used to encapsulate therapeutics in part due to their ease of use and their biocompatible nature [ 30 ]. Polymers used include alginate [ 31 , 32 ], heparin [ 33 , 34 ], chitosan [ 35 , 36 ], and carrageenan [ 37 , 38 ], among others. Alginate, a naturally derived polymer, is composed of varied amounts of β- d -mannuronate and α- l -guluronate residues linked by 1,4-glycosidic linkages [ 39 ] (M and G blocks, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…From the results, it was concluded that heparin conserved 30% of its anticoagulant activity that the half-life of docetaxel was improved with the formulation used and the growth of the MDAMD 231 cell line was inhibited greatly [47]. In other studies, doxorubicin and letrozole were used to treat this cancer type, too [48][49][50][51]. In one study, doxorubicin was combined with curcumin to be delivered by heparin modified poly(L-lactide) grafted polyethylenimine nanoparticles [52].…”
Section: Cancer Diagnosis and Therapymentioning
confidence: 99%